Tradisi Tiwah dan Tantangan Modernisasi dalam Masyarakat Dayak Ngaju - Ilham Galih Pambudi; Akbar Hidayat; Mansyur Mansyur; Rusdi Effendi; Heri Susanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Dayak people are known for their highly valued traditions, as well as their strong sense of mutual cooperation and brotherhood among their members. The Dayak people, as the indigenous people of Kalimantan Island, have many sub-tribes, one of which is the Ngaju Dayak. This article explains a tradition or traditional ceremony carried out by the Ngaju Dayak people in East Kotawaringin Regency, Central Kalimantan. The Ngaju Dayak people have a tradition called Tiwah. This tradition is interesting to study because it is a very important intangible heritage for the Ngaju Dayak people and must be passed down to the younger generation. It is a tradition that has noble values and is still carried out without diminishing its traditional values amidst the onslaught of modernization today. This research uses a historical research method. The research process consists of five stages: topic determination, heuristics or source collection, source verification or criticism, interpretation, and finally, historiography or historical writing. Data analysis and reconstruction revealed that the Tiwah tradition is a traditional ceremony of the Ngaju Dayak people, who adhere to the Kaharingan Hindu faith. This sacred ceremony is intended to send the spirits of deceased ancestors to Heaven/Lewu Tatau (the Kaharingan Hindu heaven). This traditional ceremony requires considerable expense, effort, and time, so it is held annually and is performed collaboratively by the Ngaju Dayak community. This tradition holds noble values and serves as a symbol of respect for deceased generations, community unity, and a strong sense of family.